Transnational Practices and Migrant Capital: The Case of Filipino Women in Iceland - Skaptadóttir, Unnur Dís (Social Inclusion, 2019)
Filipinos have been moving to Iceland in increasing numbers since the 1990s, primarily for employment opportunities and to reunite with relatives. They are the third largest group of immigrants in Iceland and the largest group from Asia. The majority of them work in low-income jobs in the service and production sectors where they do not utilize their education. Many arrived with the help of relatives already living in Iceland. Based on multi-sited ethnographic research, this article examines the diverse mobilization of migrant capital in Iceland and in the Philippines. The analysis draws on Bourdieu’s concepts of capital and transnational theories to highlight how Filipinos draw on formal and informal resources in Iceland and their transnational social field in mobilizing their capital. Their extended kin groups in Iceland and networks back in the Philippines are important in building migrant capital in Iceland and in the Philippines. The study shows that this mobilization is not only affected by structural factors in Iceland, such as racialization, but also by economic position and cultural capital in the Philippines.